Pelvic Artery Embolization for Treatment of Postpartum Hemorrhage - Lindquist, Jonathan D.; Vogelzang, Robert L. (Seminars in Interventional Radiology, 2018)
Postpartum hemorrhage (PPH) is the leading cause of maternal perinatal morbidity and mortality worldwide. Defined as greater than 500 mL blood loss after vaginal delivery, and greater than 1,000 mL blood loss after cesarean delivery, PPH has many causes, including uterine atony, lower genital tract lacerations, coagulopathy, and placental anomalies. Correction of coagulopathy and identification of the cause of bleeding are mainstays of treatment. Medical therapies such as uterotonics, balloon tamponade, pelvic artery embolization, and uterine-sparing surgical options are available. Hysterectomy is performed when conservative therapies fail. Pelvic artery embolization is safe and effective, and is the first-line therapy for medically refractory PPH. A thorough knowledge of pelvic arterial anatomy is critical. Recognition of variant anatomy can prevent therapeutic failure. Pelvic embolization is minimally invasive, has a low complication rate, spares the uterus, and preserves fertility.
Keywords: postpartum hemorrhage; uterine artery; embolization; fertility; interventional radiology